Recreational specialization and ecologically responsible behaviour of Chinese birdwatchers in Hong Kong. Issue 6 (3rd June 2017) - Cheung, Lewis T. O.; Lo, Alex Y. H.; Fok, Lincoln
ABSTRACT: Birdwatching is a popular nature-based recreational activity that has millions of participants worldwide. Hong Kong is an important birdwatching destination in Southeast Asia, and the number of birdwatchers visiting Hong Kong has steadily increased in recent decades. This study investigated the influences of recreational specialization on the pro-environmental attitudes and ecologically responsible behaviour of Chinese birdwatchers. Questionnaire surveys were conducted in Hong Kong, and 387 completed questionnaires were collected. The results of structural equation modelling indicate a direct positive association between the birdwatchers' specialization and pro-environmental attitudes and an indirect positive association between their specialization and ecologically responsible behaviour. These findings suggest that understanding birdwatchers' specialization is essential for predicting birdwatchers' behaviour when visiting ecologically sensitive destinations. Birdwatcher specialization levels could be used to formulate visitor management strategies at birdwatching sites and to mitigate visitor impacts on avian species.